Knowledge and Distrust May Go a Long Way in the Battle With Disinformation: Mental Processes of Spontaneous Disbelief. (August 2019) - Mayo, Ruth
A common claim is that people have an easier time accepting information than rejecting it, resulting in gullibility. In this article, I review empirical research demonstrating how the human mind is equipped with successful and spontaneous rejection processes that may protect us from disinformation.